Contested country local and regional natural resources management in Australia - Lane, Marcus B. 1966-; Robinson, Cathy J.; Taylor, Bruce (CSIRO Pub., 2009)
Leading researchers critically review Australia's environmental management over the past decade.
Keywords: Australia -- Environmental conditions.; Environmental management -- Australia.; Environmental policy -- Australia.; Sustainable development -- Australia.; Environmental protection -- Australia.; Biodiversity conservation -- Australia.; Australia.; elektronické knihy; electronic books